Gastroprotective peptide trefoil factor family 2 gene is activated by upstream stimulating factor but not by c-Myc in gastrointestinal cancer cells. Issue 5 (1st November 2002) - Al-azzeh, E; Dittrich, O; Vervoorts, J; Blin, N; Gött, P; Lüscher, B
Abstract : Background: Damage to the gastrointestinal mucosa results in the acute up-regulation of the trefoil factor family peptides TFF1, TFF2, and TFF3. They possess protective, healing, and tumour suppressive functions. Little is known about the regulation of TFF gene expression. The promoters of all three TFF genes contain binding sites (E box) for upstream stimulating factor (USF) and Myc/Max/Mad network proteins. Aims: To determine the nature and function of transcription factors that bind to these E boxes and to understand their role for TFF gene expression. Methods: TFF promoter activities were determined by reporter gene assays. DNA binding was monitored by electromobility shift assays and by chromatin immunoprecipitation analyses. Expression of endogenous TFF was determined by multiplex RT-PCR. Results: It was observed that the TFF2 promoter is specifically and efficiently activated by USF transcription factors but not by c-Myc. USF displayed comparable binding to a high affinity Myc/Max binding site compared with the three TFF E boxes, while c-Myc exhibited lower affinity to the TFF E boxes. In contrast, pronounced binding differences were observed in cells with a strong preference for USF to interact specifically with the TFF2 E box, while Myc was not above background. Exogenous expression of USF was sufficient to activate the chromosomal TFF2 and to a lesser extent, the TFF1 gene. Conclusion: These findings define USF factors as regulators of the TFF2 gene and suggest that promoter specific effects are important for a pronounced gene activation of this cytoprotective peptide.